Hadis Tentang Larangan Menghadang Dagangan Di Tengah Jalan: Studi Kritik Sanad Dan Matan - Husain, Ahmadi; Usman, Muh Ilham (Tasamuh: Jurnal Studi Islam, 2025)
This study aims to describe the Hadith about the prohibition of blocking merchandise in the road. The type of research used is library research, using descriptive-analytical methods, with a sanad and matn criticism approach. The results showed that the Hadith on the prohibition of blocking merchandise in the middle of the road from the route of Abu Daud in terms of sanad is considered muttasil or sahih. Meanwhile, in terms of the matn, there is a missing editorial or illat in it. However, it does not damage the text of the Hadith because similar traditions from different sanad lines support it. This Hadīth indicates that brokers should avoid monopolizing and cheating in trade.   Keywords: Hadith, prohibition, sanad, matn, and monopoly